Lengkung Senyum dan Tampilan Gingiva Pada Senyum - Stephany Alexandra; Wita Anggraini; Indrani Sulistyowati; Annisaa Putri Ariyani (Jurnal Kedokteran Gigi Terpadu, 2023)
A smile is a form of one's facial expression that is widely used and easy to see. Having an aesthetic and attractive smile can make a person more confident when interacting socially in their environment. There are eight main components that are assessed in a smile, two of which are the smile arc and gingiva display. Both have received a lot of attention because they are known to have a major influence on an aesthetic smile.The harmony of the smile arc and gingival display will produce an attractive smile. A consonant smile and a moderate smile line are considered the ideal smile arc and gingival display.